CONTINUING NURSE EDUCATION AS A FACTOR OF HEALTH CARE QUALITY - Yfanti, Fani; Sipitanou, Athina (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of the research was to examine the views and attitudes of nurses regarding their educational needs in the frame of Interwork Continuing Education and also explore the improvement of patient care as a result of Continuing Education. Taking into consideration the holistic and synthetic nature of Nursing science, the continuous reassessment of knowledge and skills is completely important. The results of the research showed that the participation of nurses in continuing education programs is guided by the awareness of the needs and deficiencies in the daily exercise of their profession. The training programs help to improve their working performance and efficiency. The object of education with the highest selection index was the field of Emergency Nursing followed by prevention of nosocomial infections and treating burnout. As a contribution of the study we could mention the timely and proper planning of educational programs based on the existing and future educational and training needs. Education of employees is a sustained and substantial investment in human resources and creates conditions for optimal and possible utilization of staff, based on both the needs of the service and personal knowledge and skills. Coverage of training needs through relevant training programs will lead to the improvement of health care quality, since the Continuing Education in Nursing is one of the main conditions for ensuring high level of health providers.